Bioactive peptides derived from bovine and porcine co‐products: A review. Issue 6 (22nd August 2017) - Lafarga, Tomas; Álvarez, Carlos; Hayes, Maria
Abstract: The use of meat processing co‐products to recover economically valuable food ingredients, with health‐promoting properties represents an opportunity to enhance the economic performance of the meat industry and to reduce the environmental impact of meat production. This paper discusses the potential of meat processing co‐products for use as substrates for bioactive peptide generation with varied bioactivities including antioxidant, antimicrobial, and antihypertensive properties. Moreover, the current state‐of‐art of meat‐derived bioactive peptides is reviewed with a focus on peptides with proven in vivo bioactivities. Practical applications: Meat processing co‐products represent a problem for meat processors due to the large volumes generated and its high pollutant load. These co‐products are usually used for low‐value purposes. However, co‐products such as blood or lung can be used as resources for the generation of bioactive peptides with health‐promoting properties which could be used as ingredients in the functional foods industry.